Antimicrobial Resistance and Pathogenicity of Aliarcobacter butzleri Isolated from Poultry Meat - Maria Gabriela Xavier de Oliveira; Marcos Paulo Vieira Cunha; Luisa Zanolli Moreno; André Becker Simões Saidenberg; Mônica Aparecida Midolli Vieira; Tânia Aparecida Tardelli Gomes; Andrea Micke Moreno; Terezinha Knöbl (MDPI AG, 2023)
Aliarcobacter butzleri (A. butzleri) is an emergent zoonotic food-related pathogen that can be transmitted through the consumption of poultry meat. Data regarding the pathogenicity and resistance of A. butzleri are still scarce, and the presence of virulent MDR strains of this zoonotic pathogen in poultry meat is an issue of particular concern to public health. This study aimed to characterize the pathogenicity and antimicrobial resistance profiles of A. butzleri strains isolated from poultry meat sold at retail markets in São Paulo, Brazil. The minimum inhibitory concentrations of 27 strains were determined using the broth microdilution method. The results showed that 77.7% of the isolates were resistant to clindamycin, 62.9% to florfenicol, 59.2% to nalidixic acid, 11.1% to azithromycin, 7.4% to ciprofloxacin and telithromycin, and 3.7% to erythromycin and tetracycline, although all were susceptible to gentamicin. Moreover, 55.5% of the virulent isolates were also multidrug-resistant (MDR). Three strains were selected for pathogenicity tests in vitro and in vivo. The tested strains expressed weak/moderate biofilm production and showed a diffuse adhesion pattern (3 h) in HeLa cells and toxicity in Vero cells (24 h). Experimental inoculation in 11-week-old chicks induced a transitory inflammatory enteritis. Intestinal hemorrhage and destruction of the intestinal crypts were observed in the rabbit ileal loop test. Considering the fact that Brazil is a major exporter of poultry meat, the data from this study point to the need of improvement of the diagnostic tools, as well as of the adoption of surveillance guidelines and more specific control strategies to ensure food safety, reducing the presence of pathogenic MDR strains in broilers.